Hematogones in immune thrombocytopenic purpura: diagnostic implication - Akyay, Arzu; Falay, Mesude; Oztürkmen, Seda; Biçakci, Zafer; Tavil, Betül; Ozet, Gülsüm; Olcay, Lale (The Turkish Journal of Pediatrics, 2011)
Hematogones (HGs) are benign immature B cells in bone marrow with a variety of benign and malignant conditions, including idiopathic thrombocytopenic purpura, leukemia, lymphoma, red blood cell aplasia, iron deficiency anemia, amegakaryocytosis, regenerative bone marrow following viral injury, chemotherapy or bone marrow transplantation, copper deficiency, autoimmune cytopenias, neuroblastoma, and acquired immunodeficiency syndrome (AIDS). HGs may cause diagnostic problems because of their morphologic and immunophenotypic similarities to neoplastic lymphoblasts. Herein, two patients with thrombocytopenia and three lineage dysplasias in the bone marrow suggesting myelodysplastic syndrome (MDS) with excess blasts are presented. Light microscopic evaluation of marrow from both patients revealed periodic acid-Schiff (PAS)-negative blasts However, flow cytometric analysis revealed excessive HGs in both patients, implying that the cells that were considered as blasts were actually large HGs. Thus, the patients were diagnosed as immune thrombocytopenic purpura due to the isolated thrombocytopenia, large platelets on blood and bone marrow smears and increased megakaryocytes in the bone marrow. These cases emphasize the importance of distinction of hematogone-rich conditions from leukemia and MDS for accurate diagnosis and treatment, and the reliability of multiparameter flow cytometry for the differential diagnosis.